An oligonucleotide microarray for microRNA expression analysis based on labeling RNA with quantum dot and nanogold probe - Liang, Ru-Qiang (Oxford University Press, 2005)
MicroRNAs (miRNAs) play important regulatory roles in animals and plants by targeting mRNAs for cleavage or translational repression. They have diverse expression patterns and might regulate various developmental and physiological processes. Profiling miRNA expression is very helpful for studying biological functions of miRNAs. We report a novel miRNA profiling microarray, in which miRNAs were directly labeled at the 3′ terminus with biotin and hybridized with complementary oligo-DNA probes immobilized on glass slides, and subsequently detected by measuring fluorescence of quantum dots labeled with streptavidin bound to miRNAs through streptavidin–biotin interaction. The detection limit of this microarray for miRNA was ∼0.4 fmol, and the detection dynamic range spanned about 2 orders of magnitude. We made a model microarray to profile 11 miRNAs from leaf and root of rice (Oryza sativa L. ssp. indica) seedlings. The analysis results of the miRNAs had a good reproducibility and were consistent with the northern blot result. To avoid using high-cost detection equipment, colorimetric detection, a method based on nanogold probe coupled with silver enhancement, was also successfully introduced into miRNA profiling microarray detection.